ChemInform Abstract: Rapid Synthesis and Effect of High Temperature and High Pressure Processing on the Structure and Thermoelectric Properties of Clathrate Ba8Cu6Si16Ge24. Issue 9 (February 2016) - Sun, Bing; Jia, Xiaopeng; Huo, Dexuan; Sun, Hairui; Zhang, Yuewen; Liu, Binwu; Liu, Haiqiang; Kong, Lingjiao; Ma, Hongan
Abstract: The title clathrate is synthesized from a stoichiometric mixture of the elements and BaSi2 (3—5 GPa, 1125 K, 30 min).